2002
DOI: 10.1177/154405910208101013
|View full text |Cite
|
Sign up to set email alerts
|

Is Reduction of Pocket Probing Depth Correlated with the Baseline Value or is it “Mathematical Coupling”?

Abstract: Previous studies using correlation or regression analysis have showed that treatment effects measured by the change in clinical parameters are often associated with baseline values of the same parameters. These studies, however, have a methodological weakness. Correlation/regression between baseline measures and the derived change variable invalidates the statistical procedures of testing the null hypothesis: that the coefficient of correlation/regression is zero. This is due to the phenomenon of mathematical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 21 publications
(22 reference statements)
2
35
0
Order By: Relevance
“…46 Such adjustments may in turn lead to misleading inferences regarding the adjusted associations between outcomes and explanatory variables. 47 This is particularly likely to be the reason for the reduced (non-significant) regression coefficient for the relationship between gestational age and pulse pressure after adjustment for mean 24-h systolic blood pressure, which was highly correlated with pulse pressure (r ¼ 0.87). This raises the possibility that pulse pressure may be acting as a surrogate for 24-h systolic blood pressure, particularly as there is no significant change in diastolic blood pressure with gestation, which would serve to distort the ratio determining pulse pressure.…”
Section: Discussionmentioning
confidence: 99%
“…46 Such adjustments may in turn lead to misleading inferences regarding the adjusted associations between outcomes and explanatory variables. 47 This is particularly likely to be the reason for the reduced (non-significant) regression coefficient for the relationship between gestational age and pulse pressure after adjustment for mean 24-h systolic blood pressure, which was highly correlated with pulse pressure (r ¼ 0.87). This raises the possibility that pulse pressure may be acting as a surrogate for 24-h systolic blood pressure, particularly as there is no significant change in diastolic blood pressure with gestation, which would serve to distort the ratio determining pulse pressure.…”
Section: Discussionmentioning
confidence: 99%
“…25 Such adjustments may in turn lead to Birth weight and pulse pressuremisleading inferences regarding the adjusted associations between outcomes and explanatory variables. 26 This is particularly likely to be have the reason for the reduced coefficient for the relationship between birth weight and pulse pressure after adjustment for systolic blood pressure, which was highly correlated with pulse pressure. This also raises the possibilities that pulse pressure may be acting as a surrogate for systolic blood pressure, or that systolic blood pressure lies on the causal pathway between fetal growth and pulse pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Results from the regression analysis revealed that treatment outcomes were significantly associated with baseline HDD in both treatment groups. As there is mathematical coupling [3][4][5] between baseline HDD and the outcome, horizontal bone fill (ie change in HDD), further statistical analyses are warranted to support this purported association. In general, mathematical coupling occurs when one variable directly or indirectly contains the whole or part of another, and the two variables are then analysed using correlation or regression, 4 such as investigating the relation between change or percentage change in variables (eg following an intervention) and their initial/baseline values (ie prior to the intervention).…”
Section: Example Three: Horizontal Bone Fill and Pocket Depth Clinicmentioning
confidence: 99%
“…In general, mathematical coupling occurs when one variable directly or indirectly contains the whole or part of another, and the two variables are then analysed using correlation or regression, 4 such as investigating the relation between change or percentage change in variables (eg following an intervention) and their initial/baseline values (ie prior to the intervention). [3][4][5] Consequently, the statistical procedure of testing the null hypothesis -that the coefficient of correlation or the slope of regression is zero -becomes inappropriate.…”
Section: Example Three: Horizontal Bone Fill and Pocket Depth Clinicmentioning
confidence: 99%
See 1 more Smart Citation